2022
DOI: 10.3390/healthcare10081495
|View full text |Cite
|
Sign up to set email alerts
|

Antigenicity Preservation Is Related to Tissue Characteristics and the Post-Mortem Interval: Immunohistochemical Study and Literature Review

Abstract: The main aim of this study was to investigate the post-mortem proteolytic degradation process of selected tissue antigens and correlate it to the post-mortem interval. During the autopsy of 12 cadavers (time interval ranging 1 day–2 years after death) samples of skin, liver, kidney, and spleen were collected. All samples were formalin-fixed and paraffin-embedded. Four µm paraffin sections were used for hematoxylin–eosin staining and immunohistochemical analysis (Ki67, Vimentin, Pan cytokeratin, and CD20). Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The reliability of the encephalogram (EEG) to confirm brain death remains, nevertheless, controversial. Indeed, several studies have shown that brain electrical activity persists for up to 72 h after the person is declared dead [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reliability of the encephalogram (EEG) to confirm brain death remains, nevertheless, controversial. Indeed, several studies have shown that brain electrical activity persists for up to 72 h after the person is declared dead [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The immunohistochemical (IHC) technique is based on antibodies against specific antigens in tissues and cells. In histopathology, IHC testing is most commonly performed on formalin-fixed, paraffin-embedded tissues that can be stored for long periods of time [ 135 , 136 ]. Increasingly, tissue microarrays (TMAs), which contain selected tissue material from tumors, normal tissues (control), and tumor metastases on a single slide, are being used for IHC.…”
Section: Methods To Assess Cell Proliferation In Colorectal Cancermentioning
confidence: 99%
“…There is a lack of standardized systems for evaluating performance, relying on different cut-off values and inconsistent criteria to define the threshold value of marker/antigen positive expression by IHC. A lower reproducibility of results may also be affected by differences in the preparation conditions, antibodies used, their dilutions, and IHC reaction detection systems [ 135 , 136 , 198 , 210 ]. Automated IHC measurements promise to overcome these limitations.…”
Section: Methods To Assess Cell Proliferation In Colorectal Cancermentioning
confidence: 99%